Placement events in the bilingual mind : the verbal and gestural expression of placement by Afrikaans-English bilinguals - Gultzow, Runa Simone (Stellenbosch : Stellenbosch University, 2025)
Thesis (DPhil)--Stellenbosch University, 2025.